Reinventing energy efficiency for net zero - Rosenow, J; Eyre, N (Elsevier, 2022)
Energy efficiency has delivered the largest share of historic greenhouse gas mitigation. A significant part of this relied on replacing fossil fuel technologies with more efficient versions, often supported by public funding or driven by other policies and regulations. But the goalposts have shifted dramatically in recent years. The scale of the climate crisis means that full decarbonisation of the economy rather than partial reduction of emissions is now the target. Instead of just using fossil fuels more efficiently, this requires ceasing using them at all. This in turn requires moving to zero‑carbon energy vectors, notably via electrification of end-uses previously not served by electricity. At the same time, the costs of renewable electricity sources and storage have plummeted and are expected to continue to fall further. The combined effects have major implications for the role of energy efficiency in energy system change. In this paper, we assess whether and how energy efficiency can and needs to be reinvented in light of these challenges. We identify a number of policy recommendations suggesting that energy efficiency needs to continue to play an important role, but can only do so if we rethink its role in the race towards full decarbonisation.